Attitudes of representatives of major religious movements towards the digitalisation of religion - M. Ja. Yuldashev; A. I. Ivanchenko; O. A. Kulikova (Вестник университета)
The Internet has become an integral part of the modern society. It has a strong influence on the social institutions and makes them adapt to the new conditions of the digital environment. Religion is not an exception despite its inherent resistance to change; such an ancient social construct was also forced to enter the process of digitalisation. The article reflects the peculiarities of this process: it analyses the activities of various religious movements in the Russian Federation in the digital environment and reveals the attitude of religious representatives (official and unofficial) to the process of adapting religion to the digital environment. The scholarly literature on the digitalisation of religion was analysed and the problematic aspects of this process were identified. A content analysis of the Internet communities and resources of the main traditional (Orthodoxy, Islam and Judaism) and non-traditional religious teachings (Neopaganism and Satanism)was carried out. We identified the attitude of religious representatives to the digitalisation of religion. We conducted an expert interview with bloggers whose activities are related to the dissemination of religious views on the Internet.